If a+b+c=0 then find
b 2 − c a b 2 + c 2 + a 2
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
It is given that a + b + c = 0 ⇒ b = − ( a + c ) .
⇒ b 2 − c a b 2 + c 2 + a 2 = [ − ( a + c ) ] 2 − c a [ − ( a + c ) ] 2 + c 2 + a 2 = c 2 + 2 c a + a 2 − c a c 2 + 2 c a + a 2 + c 2 + a 2
= c 2 + c a + a 2 2 c 2 + 2 c a + 2 a 2 = c 2 + c a + a 2 2 ( c 2 + c a + a 2 ) = 2
let us assume that a=3,b=1,c=-4 so that it satisfies a+b+c=0 if we substitute the same a,b,c values in (b^2+c^2+a^2)/(b^2-ca) then we will get 2 as a result in case if we consider another values fora,b,c also then we will get 2 as the final result we can take a=4,b=1,c=-5; a=6,b=1,c=-7 .....................so on
yeah i got it
let us assume that a=3,b=1,c=-4 so that it satisfies a+b+c=0 if we substitute the same a,b,c values in (b^2+c^2+a^2)/(b^2-ca) then we will get 2 as a result in case if we consider another values fora,b,c also then we will get 2 as the final result we can take a=4,b=1,c=-5; a=6,b=1,c=-7 .....................so on
Problem Loading...
Note Loading...
Set Loading...
( a + b + c ) 2 = 0
a 2 + b 2 + c 2 + 2 ( a b + b c + a c ) = 0
a 2 + b 2 + c 2 = − 2 ( b ( a + c ) + a c )
a 2 + b 2 + c 2 = − 2 ( − b 2 + a c )
a 2 + b 2 + c 2 = 2 ( b 2 − a c )
put in the equation and answer is 2